Efektivitas Latihan Relaksasi Autogenik terhadap Intensitas Nyeri pada Pasien Pascaoperasi Fraktur - Jismer Panjaitan; Dudut Tanjung; Sumaiyah Sumaiyah (Journal of Telenursing (JOTING), 2023)
This study aims to identify the effectiveness of autogenic relaxation exercises on pain intensity in post-operative fracture patients at Advent, Royal Prima, and Murni Teguh Medan Hospitals. This research method is a quasi-experiment with a non-equivalent control group design. Sampling used non-probability sampling with the convenience sampling method. The respondents in this study were 24-hour post-surgical fracture patients who were hospitalized, totaling 78 respondents consisting of 39 respondents in the intervention group and 39 respondents in the control group. Data analysis used Mann-Whitney statistical test analysis. The results showed that p-value = 0.000 (p<0.05). In conclusion, autogenic relaxation exercises are effective in reducing pain intensity in patients after fracture surgery and are recommended as a nursing intervention and alternative therapy to reduce pain intensity in patients after fracture surgery. Keywords: Autogenic Relaxation Exercise, Fracture, Pain.